2015
DOI: 10.1185/03007995.2015.1062357
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blocker use in severe sepsis and septic shock: a systematic review

Abstract: Recent growing evidence suggests that beta-blocker treatment could improve cardiovascular dynamics and possibly the outcome of patients admitted to intensive care with severe sepsis or septic shock

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 65 publications
2
56
0
2
Order By: Relevance
“…While it is theoretically plausible, experimental and clinical studies yielded conflicting results (5)(6)(7)48,49). Observational studies showed that esmolol, the most commonly used beta-blocker in septic shock, was associated with economization of cardiac work and oxygen consumption.…”
Section: Beta-blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is theoretically plausible, experimental and clinical studies yielded conflicting results (5)(6)(7)48,49). Observational studies showed that esmolol, the most commonly used beta-blocker in septic shock, was associated with economization of cardiac work and oxygen consumption.…”
Section: Beta-blockersmentioning
confidence: 99%
“…Since it remains largely unknown whether such response is an adaptation to noxious stimulus or a maladaption to it, a variety of drugs have been used for the management of cardiovascular presentations of sepsis, severe sepsis or septic shock (5)(6)(7). In this review, we aimed to discuss vasoactive agents that can be used to treat sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Beta-blockade has been associated with reduced mortality during septic shock in experimental studies and in two preliminary human RCTs [6][7][8]. A recent small pilot RCT (n = 90) in China suggested benefit of the combination of esmolol and milrinone in sepsis for control of heart rate and possibly survival (but the absolute risk reduction was an unlikely 30 %) [6].…”
mentioning
confidence: 99%
“…Retrospective cohort studies suggest that chronic use of beta-blockers prior to ICU admission improves short-term survival [9]. A recent systematic review of beta-blockade in sepsis suggests some benefit, but there is still work to do because of the lack of large RCTs-most studies are small and uncontrolled case series/cohorts [7]. In addition to its beneficial effects on cardiac dynamics, beta-blockade may exert beneficial pleiotropic effects including blunting the inflammatory response, metabolic changes, and sepsis-associated coagulopathy [10][11][12][13][14].…”
mentioning
confidence: 99%
“…In the present issue of CMRO, Sanfilippo et al 1 discuss the results of a systematic review on the use of beta blockade in patients with severe sepsis or septic shock. The authors found only two randomized controlled trials (RCTs) including a total of 195 patients, a few small prospective and retrospective studies and several experimental studies.…”
mentioning
confidence: 99%